Controlling cancer cell fate using localized biocatalytic self-assembly of an aromatic carbohydrate amphiphile - Pires, R. A. (2015)
We report on a simple carbohydrate amphiphile able to self-assemble into nanofibers upon enzymatic dephosphorylation. The self-assembly can be triggered by alkaline phosphatase (ALP) in solution or in situ by the ALP produced by osteosarcoma cell line, SaOs2. In the latter case, assembly and localized gelation occurs mainly on the cell surface. The gelation of the pericellular environment induces a reduction of the SaOs2 metabolic activity at an initial stage (≤ 7 h) that results in cell death at longer exposure periods (≥ 24 h). We show that this effect depends on the phosphatase concentration, and thus, it is cell-selective with prechondrocytes ATDC5 (that express ∼ 15−20 times lower ALP activity compared to SaOs2) not being affected at concentrations ≤ 1 mM. These results demonstrate that simple carbohydrate derivatives can be used in an antiosteosarcoma strategy with limited impact on the surrounding healthy cells/ tissues.